3x^3 -3x^2 -18x = 3x(x^2 -x -6) = 3x(x-3)(x+2) so the 3rd choice is right sure
hope helped
given f)x) then
- f(x) represents a reflection in the x-axis
f(x + 4 ) represents a shift of 4 units horizontally to the left
f(x) + 12 represents a vertical shift of 12 units down
thus h(x) = f(x + 4 ) - 12
is the graph of f(x), moved 4 units left, 12 units down and reflected in the x- axis
The answer is 2 be 8/16 is 2
Answer:
the solution of linear equation 4b + 6 = 2 - 6 + 4 is b = -2
Step-by-step explanation:
We need to solve the linear equation
4b + 6 = 2 - 6 +4
Adding constants
4b + 6 = 0
Adding -6 on both sides
4b + 6 -6 = 0 -6
4b = -6
Dividing with 4 on both sides
4b/4 = -6/4
b = -2
So, the solution of linear equation 4b + 6 = 2 - 6 + 4 is b = -2